PsycEXTRA Dataset 2017
DOI: 10.1037/e507482017-001
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Sense Of Coherence In Stressor Appraisal

Abstract: According to the transactional theory of stress, cognitive individual differences impact stressor appraisal. Sense of Coherence (SoC) refers to an individual's generalized perception of environmental stimuli. Individuals with a strong SoC perceive the world as more comprehensible, manageable, and meaningful and may be more likely to appraise work-related stressors as having potential for opportunities (challenges) than for obstructing personal gain (hindrances) or causing harm (threats). This study assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 95 publications
(134 reference statements)
1
9
0
Order By: Relevance
“…I discovered no study intending to measure all three appraisal outcomes. But Brady's (2017) findings in the USA on challenge, hindrance and threat appraisal are consistent with the predictions of H3, and all three studies by Braun-Lewehsohn and her colleagues (2011,2018,2019) provide support for the danger dimension in H3.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…I discovered no study intending to measure all three appraisal outcomes. But Brady's (2017) findings in the USA on challenge, hindrance and threat appraisal are consistent with the predictions of H3, and all three studies by Braun-Lewehsohn and her colleagues (2011,2018,2019) provide support for the danger dimension in H3.…”
Section: Discussionsupporting
confidence: 76%
“…So, there is some evidence supportive of H3, but only indirectly so. The measures used by Brady (2017) and Braun-Lewehsohn and colleagues (ibid) were not selected explicitly to test H3. But it may be that indirect tests are all that can be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent examples of this demand category are concerns with job security (Cavanaugh et al, 2000) and role ambiguity (Tuckey et al, 2015). Being present in most work environments and experienced across different occupations (Wiegand et al, 2012;Brady and Cunningham, 2019), both job hindrances have been found to have negative consequences for employee's attitudes and their health (Rizzo et al, 1970;Sverke et al, 2002;Schmidt et al, 2014). In contrast, job challenges are referred to as "work-related demands or circumstances that, although potentially stressful, have associated gains for the individuals" (O'Brien and Beehr, 2019, p. 963).…”
Section: The Amended Job Demands-resources Modelmentioning
confidence: 99%
“…An experimental study among undergraduate students examined the differential relations of threats and hindrances on performance outcomes (Espedido and Searle, 2018). Moreover, a recent cross-sectional study among full-time workers and students working part-time successfully included the concept of threat stressors when examining common psychosocial workplace stressors (Brady and Cunningham, 2019). Yet, most research conducted within the field of occupational health continues to apply the C-H perspective to the examination of work-related stressors, equalizing hindrances with threats (Tuckey et al, 2015;Espedido and Searle, 2018).…”
Section: The Amended Job Demands-resources Modelmentioning
confidence: 99%